Boundary Value Problems for Impulsive Fractional Evolution Integrodifferential Equations with Gronwall’s Inequality in Banach Spaces - Chalishajar, Dimplekumar N.; Karthikeyan, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we study boundary value problems for impulsive fractional evolution integrodifferential equations with Caputo derivative in Banach spaces. A generalized singular type Gronwall inequality is given to obtain an important priori bounds. Some sufficient conditions for the existence solutions are established by virtue of fractional calculus and fixed point method under some mild conditions. An example is given to illustrate the results.